The Australian East-West Radio Relay System Revisited: Thermal Design of Repeater Shelters - Moorhead, Simon (Journal of Telecommunications and the Digital Economy, 2024)
The Journal revisits two historic papers from 1971 covering the thermal design and environmental controls in repeater shelters of the Australian East-West radio relay system from Northam in Western Australia to Port Pirie in South Australia.